Goat agribusiness extension in Komala Village, South Wangi-Wangi District - Hafid, Harapin; Anfas, Anfas; Dedu, La Ode Arfan; Aku, Achmd Selamet; Ananda, Siti Hadrayanti; Astarika, Rina (Journal of Saintech Transfer, 2025)
The Komala Village community has many goats but there are many problems faced by the community such as dead fetuses, malnutrition, limited health care, environmental conditions, lack of knowledge and training and limited infrastructure. Therefore, the aim of this extension activity is to provide education to the farming community about the correct way to raise goats. This activity was carried out on Friday, March 26, 2023 at 16.00 WITA - Finish, located at the Gazebo of the Komala Village Head's House, South Wangi-Wangi District, Wakatobi. Counseling materials presented to the community: (1) Types of appropriate and balanced feed for goats, (2) Natural feed, supplementary feed, and fermented feed, (3) How to organize feeding according to age, weight, and maintenance objectives, (4) Efficient feeding methods, and (5) Mixing and serving feed techniques. After following the goat farming extension, the community response was as follows: (1) enthusiasm and participation, (2) increased understanding, (3) interest in new practices, (4) awareness of the importance of improving goat rearing practices (5) satisfaction with information, (6) positive perception of benefits, (7) desire for further training, and (8) better collaboration. The conclusion from this community service activity is that the community in Komala Village still has low knowledge regarding how to raise goats. Although they have experience in raising goats, many things can still be improved in farming practices to achieve better results. As for what needs to be improved in community knowledge, such as feed management, care, production management, use of technology, and business management skills.